Census of Medical Examiners' and Coroners' Offices, 2004 ([Verlag nicht ermittelbar], 2007)
The Census of Medical Examiners' and Coroners' Offices (MECO) is a compilation of data on the practices of these offices, which are responsible for medical-legal death investigations. The data cover information such as the prevalence of unidentified human remains on record in medical examiners' and coroners' offices across the country, record-keeping practices, and final disposition practices such as burial, cremation, or other means. In addition, data were gathered on FTE employees, contractors, and annual budgets.